Nanomaterials enhanced surface plasmon resonance for biological and chemical sensing applications - Zeng, Shuwen (2014)
The main challenge for all electrical, mechanical and optical sensors is to detect low molecular weight (less than 400 Da) chemical and biological analytes under extremely dilute conditions. Surface plasmon resonance sensors are the most commonly used optical sensors due to their unique ability for real-time monitoring the molecular binding events. However, their sensitivities are insufficient to detect trace amounts of small molecular weight molecules such as cancer biomarkers, hormones, antibiotics, insecticides, and explosive materials which are respectively important for early-stage disease diagnosis, food quality control, environmental monitoring, and homeland security protection. With the rapid development of nanotechnology in the past few years, nanomaterials-enhanced surface plasmon resonance sensors have been developed and used as effective tools to sense hard-to-detect molecules within the concentration range between pmol and amol. In this review article, we reviewed and discussed the latest trend and challenges in engineering and applications of nanomaterials-enhanced surface plasmon resonance sensors (e.g., metallic nanoparticles, magnetic nanoparticles, carbon-based nanomaterials, latex nanoparticles and liposome nanoparticles) for detecting “hard-to-identify” biological and chemical analytes. Such information will be viable in terms of providing a useful platform for designing future ultrasensitive plasmonic nanosensors.